APPLICATION OF RESTORATIVE JUSTICE IN DISPUTE RESOLUTION OF TRADEMARK CRIMES IN THE POLICE (STUDY OF THE NORTH SUMATRA REGIONAL POLICE) - Tri Febriana Sinaga; Maswandi Maswandi; Azwir Agus (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Restorative justice is an approach in the criminal justice system that focuses on victim recovery, perpetrator rehabilitation, and community recovery that aims to create a more holistic solution by involving all parties affected by the crime in the settlement process. The formulation of the problem in this study is how the regulation of restorative justice in the North Sumatra Regional Police, how the mechanism for resolving brand crimes in the police, and how the application of restorative justice in the North Sumatra Regional Police in brand crimes. The purpose of this study is to review and analyze the regulation of Restorative Justice in the North Sumatra Regional Police, analyze and analyze the mechanism for resolving brand crimes in the Police, and analyze and analyze the application of Restorative Justice in the North Sumatra Regional Police in Brand Crimes. This type of research uses normative juridical research that is descriptive-analytical and qualitative analysis. The results of the study explain the regulation of restorative justice in the North Sumatra Regional Police, there are various regulations such as the old Criminal Code, the Police Law, the Decree of the Chief of Police No. Pol: B / 3022 / XII / 2009 / SDEOPS concerning Handling Cases Through Alternative Dispute Resolution, Perkapolri No. 8 of 2021 concerning Handling Criminal Acts Based on Restorative Justice and Law No. 1 of 2023 concerning the National Criminal Code and Law No. 25 of 2025 concerning the New Criminal Code. Meanwhile, the mechanism for resolving trademark crimes in the police is carried out through mandatory complaints from victims and investigations by the police to resolve trademark crimes in the police. Regarding the application of restorative justice in trademark crime cases by the North Sumatra Regional Police, not a single case can be resolved using a restorative justice approach because there are key factors, namely legal, social, and cultural factors.